AESTHETIC VS ARTISTIC CONSCIOUSNESS: TYPOLOGY OF AESTHETICS AND LITERATURE INTERACTION - Anna A. Stepanova; Ilona V. Dorohan (Alfred Nobel University Journal of Philology, 2023)
The objective of the work is to study the specifics of aesthetic and artistic consciousness in their interaction in terms of literary comprehension of philosophical concepts; to highlight the levels of interaction between aesthetics and literature as a factor in the formation of aesthetic dominants of the literary trend and artistic method. The focus of the work determines the use of cultural-historical, historicalliterary, philosophical and aesthetic research methods. Aesthetic consciousness is understood as a mode of intellectual-sensory perception (and assessment) of empirical reality, which determines the type of artistic consciousness and is reflected in a work of fiction. Three levels of correlation between aesthetic consciousness and reality are distinguished: the syncretic, at which the aesthetic consciousness merges with the empirical, dissolving into reality, and the ideal of beauty corresponds to scientific ideas about the surrounding world and man; the discrete level emphasises a certain autonomy of aesthetic consciousness from empirical one, its orientation towards the expression of some ideological or ideal essence; the synthetic, representing dialectical interaction and mutual influence, giving rise to harmony and aesthetic value of the unity of content and form. The specificity of the relationship between aesthetic and artistic consciousness is determined. The process of interaction between aesthetic and artistic consciousness as the interaction between aesthetics and literature takes place at two levels. The first level represents the transformation of the system of aesthetic-philosophical theories and characterises the state of aesthetic consciousness as a set of aesthetic views of the epoch. The second level is characterised by the process of “the transition of the artistic to the general cultural”, involving a change in worldview stereotypes when literature, producing its own spiritual values and anti-values, turns out to be able to reorient public consciousness (in some instances, even scientific) and public psychology, to shape the mindset, tastes, and specifics of everyday culture. The findings note that the convergence of aesthetic consciousness and literature, along with the actualisation of the principle of possibilities that began in the Romantic era, largely predetermined the development of aesthetic consciousness at the turn of the 19th and 20th centuries, when their interaction became so intertwined that it formed a unity. The distinction between aesthetics and literature practically disappeared, ushering in a new stage of cultural reorientation for aesthetics and art.